BIAYA KECELAKAAN LALULINTAS JALAN DI INDONESIA DAN VIETNAM - Sugiyanto, Gito (Jurnal Transportasi, 2010)
The aim of this study is to analyze the characteristics and to estimate the cost of road accidents in Banyumas, Indonesia, and in Vietnam. The accident cost in Indonesia consists of direct and indirect costs, while the accident cost in Vietnam consists of tangible and intangible costs. The results show that the characteristics ofroad accidents in Indonesia are similar to those in Vietnam, with most accidents were caused by men. In addition, the road accident cost in Indonesia is much higher that that of Vietnam.Keywords: accident cost, direct and indirect costs, tangible and intangible costs